Accounting in Critical Paradigm (Vallis Aurea, 2021)
This article discusses the critical paradigm in accounting research. Accounting can be included in the critical paradigm. Critical paradigm offers a holistic approach and avoid deterministic and reductionistic thinking. Critical paradigm always see the social reality in a historical perspective, using both objective and subjective approach in looking at social change. At the end, in addition to discussing qualitative methods in critical research, this article also tries to conduct a brief discuss of review articles in the critical paradigm.